Effects of Dates of Sowing, Spacing and Seed Rate on Flowering, Seed Yield and Quality of Sunnhemp - ASHOK TIPARADDI; N.K. BIRADARPATIL; M. SHEKHARGOUDA (Seed Research, 2026)
Sowing of sunnhemp during 2nd fortnight of August recorded significantly higher number of pods per plant (46.18), seeds per pod (10.02) and seed yield per ha (836.8 kg) as compared to 1st fortnight of September. Row spacing of 30 cm recorded significantly higher number of pods per plant (42.62), seeds per pod (9.82) and seed yield per ha (770.1 kg) over wider row spacing of 45 cm. The seed rates of 15 kg per ha (753.5 kg/ha) and 20 kg per ha (680.2 kg/ha). Early sowing, closer row spacing and lower seed rate delayed the flowering.